Do vasomotor and genitourinary symptoms of menopause vary between sedente and migrant groups? A study on the Oraon tribal populations of Eastern India. Issue 5 (9th December 2021) - Thakur, Joyeeta; Goswami, Monali; Roy, Subho
Abstract: Objectives: Human reproductive characteristics are embedded within local ecological contexts. A shift in the local ecology is likely to offer challenges in reproductive outcome. We aimed to investigate sedente–migrant variation in experiencing vasomotor and genitourinary symptoms at perimenopausal and postmenopausal stages and its concomitants. Methods: Four hundred Oraon tribal populations living in Eastern India (sedente [100 each from perimenopausal and postmenopausal groups] and migrants [100 each from perimenopausal and postmenopausal groups]) were studied. Data on vasomotor and genitourinary symptoms, socio‐demographic and reproductive history, body compositions, lifestyle variables, and energy intake were compared between sedente and migrant independently for perimenopausal and postmenopausal groups. Principal component analysis (PCA) was used to identify the principal components (PCs) of menopausal symptoms. A two level multilevel linear regression was applied independently for perimenopausal and postmenopausal groups to identify the concomitants of menopausal symptoms and estimate sedente–migrant variance. Results: Bivariate analysis showed significant ( p  ≤ .05) sedente–migrant differences in socio‐demographic, reproductive, body composition, energy intake, and lifestyle variables and in some of the vasomotor and genitourinary symptoms. In multilevel analyses, random effect did not show significant heterogeneity between sedente and migrant groups in experiencing menopausal symptoms; however, fixed effect showed that region from which participants were recruited (Gram Panchayat [GP]) and individual level characteristics were concomitants ( p  ≤ .05) for menopausal symptoms, irrespective of menopausal status. Conclusion: Variability at GP levels and individual level characteristics of sedente and migrant groups predominantly determined menopausal symptoms of the study populations, but not the migration status.